2007
DOI: 10.1136/jcp.2006.040386
|View full text |Cite
|
Sign up to set email alerts
|

Indefinite for non-invasive neoplasia lesions in gastric intestinal metaplasia: the immunophenotype

Abstract: Background: In the Padova International Classification, gastric precancerous lesions are labelled as ''indefinite for non-invasive neoplasia'' (Indef-NiN) cytohistological alterations mimicking non-invasive neoplasia (NiN), but lacking all the attributes required for a definite NiN categorisation. Aim: To apply a panel of immunohistochemical (IHC) markers of cell proliferation (Mib1), intestinal differentiation (Cdx2), apoptosis (pro-caspase 3) and cell immortalisation (hTERT) to compare the IHC profiles of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
1
13
0
6
Order By: Relevance
“…The results showed that Ab 3 (NCL-L-hTERT antibody) was not absorbed any more with the nucleolin peptide than were the other anti-hTERT antibodies. In agreement with other researchers (27,70,71,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97) and despite the objection raised by Wu et al (64) the Ab 3 proved suitable for hTERT detection. Mitsuishi et al (98) not only confirmed the consideration of Wu et al (64), but also found excellent correlation between nucleolin expression and telomerase activity levels in Bowens's disease and in normal sunexposed skin.…”
Section: Comparison Of Htert Results In Basal Cell Carcinomas and Squsupporting
confidence: 76%
“…The results showed that Ab 3 (NCL-L-hTERT antibody) was not absorbed any more with the nucleolin peptide than were the other anti-hTERT antibodies. In agreement with other researchers (27,70,71,(88)(89)(90)(91)(92)(93)(94)(95)(96)(97) and despite the objection raised by Wu et al (64) the Ab 3 proved suitable for hTERT detection. Mitsuishi et al (98) not only confirmed the consideration of Wu et al (64), but also found excellent correlation between nucleolin expression and telomerase activity levels in Bowens's disease and in normal sunexposed skin.…”
Section: Comparison Of Htert Results In Basal Cell Carcinomas and Squsupporting
confidence: 76%
“…Among the 50 tested genes, TP53 was the best candidate as a diagnostic and prognostic biomarker of gastric epithelia transformation from dysplasia to early invasive cancer. Previous studies demonstrated loss of heterozygosis at the TP53 locus in 14 % of a series of gastric intestinal metaplasia and in 22 % of gastric dysplastic lesions [17]. In our series, 6 of 9 EGC-coexisting HG-IEN lesions were TP53 mutated, and p53 overexpression increased with the increasing severity of the precancerous lesion in an independent set of 75 biopsy specimens.…”
Section: Discussionmentioning
confidence: 47%
“…Moreover, most of the limited amount of material obtained from upper GI endoscopy is required for histopathological characterization of the specimen. As a result, there is still no molecular marker used in clinical practice to distinguish HG-IEN from early invasive neoplasia [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al (106) conclude from their studies on culture cells and tissues fixated in formalin that chicken IgG antibodies can have definite advantages over the commonly used mammal IgG antibodies and exhibit less non-specific staining. Irrespective of the afore-mentioned objections, many authors continue to use the monoclonal NCL-L-hTERT for immunohistochemical proof of hTERT (63,66,(107)(108)(109)(110)(111)(112).…”
Section: Cells Which May Be Responsible For Telomerase Activity Outsimentioning
confidence: 99%